Pemberdayaan Kreativitas Masyarakat Melalui Pembuatan Bola-Bola Coklat dan Bouqet Uang sebagai Penguatan Wirausaha Santripreneur di Pesantren Pondok Pesantren Salafiyah Al Choliliyah Pasuruan - Hidayah Almubarokah, Nurul; Hanifah, Umi; Mukaromah, Ning; Azis, Abd. (Yayasan Pusat Kemanusiaan dan Transformasi Sosial, 2024)
This study aims to examine the empowerment of community creativity through the creation of chocolate balls and bouquet money as an effort to strengthen santripreneurship in Pondok Pesantren Salafiyah Al Choliliyah Pasuruan. By focusing on practical skills in the production of creativity-based products, this research demonstrates that these activities not only introduce entrepreneurial skills but also provide economic opportunities for the santri and the surrounding community. Additionally, the training and mentoring provided in making chocolate balls and bouquet money can enhance self-confidence, creativity, and the ability of santri to develop businesses based on local potential. The results of this study are expected to strengthen the pesantren economy and create independent and competitive santripreneurs.